Factors shaping supplydemand relations on the fruit and vegetable market in the light of the behavior of groups and producer organizations - Czyżewski Andrzej; Bieniek-Majka Maryla; Czakowski Dariusz (Management, 2018)
Factors shaping supply-demand relations on the fruit and vegetable market in the light of the behavior of groups and producer organizations The authors have addressed the question to what extent the functioning of groups and organizations of fruit and vegetable producers depends on the market situation, the authors presented the shaping of supply-demand relations on the fruit and vegetable market in Poland in 2008-2016. They drew attention to the decreasing area of land intended for horticultural crops, with the simultaneous increase in the size of supply. They presented changing productive structures and showed changes in the market share of fruit and vegetable producer groups and organizations. They noticed that the market situation (prices, demand, costs, embargo) caused that the number of fruit and vegetable producers’ groups and organizations on the market decreased, which was reflected in the market situation.